Jude the obscure - Hardy, Thomas, 1840-1928.; Vance, Norman; Wordsworth Classics (London : Wordsworth Classics, 2000)
The story of Jude Fawley, an impoverished stonemason who aspires to the ministry and fails to fulfill the opposite expectations of the two women he loves in Victorian society.
Includes bibliographical references.
Adult
Keywords: Adultery -- Fiction; Children -- Death -- Fiction; Illegitimate children -- Fiction; Stonemasons -- Fiction; Unmarried couples -- Fiction; Didactic fiction; Illegitimacy -- Fiction; Love stories; Wessex (England) -- Fiction